Facilitating or Blurring: Exploring the Influence of Technology on Work Life Balance in the Indian Hotel Industry ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: Hotels are increasingly adopting smart technology to boost operational efficiencies, which has  effectively reduced employees’ manual workload, it also presents potential negative consequences for work-life balance.  Technology’s influence on employee work-life balance is critical for addressing emerging stressors, enhancing overall  well-being, and improving retention within the hotel industry. Objectives: This study aims to explore the influence  of technology on the work-life balance of Indian hotel industry employees and suggest the scope for improvement  concerning the use of technology at the workplace. Methodology: This quantitative study employed a purposive sampling  technique to collect data from 128 hospitality professional working in various departments of the hotel industry across  India, via a structured questionnaire. Descriptive statistics summarized respondent demographics, while Spearman’s  Rank-Order Correlation assessed relationships between technology use perceptions and work-life balance. All analyses  were performed using Python. Results: The study revealed that 52% of respondents agreed or strongly agreed that  technological tools contributed to reducing workload, and majority of the participants (64%) responded that it improves  communication, and simplifying schedule management. However, the findings also highlighted negative consequences,  including increased stress (47%), blurred work-life boundaries (51%), and a perceived pressure to remain constantly  available (52%). Therefore, most of the participants propose the introduction of flexible work schedules, automation of  routine tasks, and implementation of clear availability guidelines. Conclusion: Greater flexibility in work schedules,  clearer availability guidelines, and the automation of routine tasks emerged as key technological changes preferred for  improving employee’s work-life balance in the Indian hotel industry.
Keywords: Work life balance; technostress; hotel industry; technological advancements